The Influence of Quick Ratio, Return on Asset, Debt to Equity Ratio, and Total Asset Turnover on Company Value - Haryati, Sari Sri; Hakim, Astrid Dita Meirina (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of Quick Ratio, Return On Assets, Debt to Equity Ratio, and Total Asset Turnover on Company Value in the automotive sub-sector listed on the Indonesia Stock Exchange for 2018 - 2022. The sample for this study was 16 automotive sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research was conducted using the panel data regression method assisted by the Eviews 10 program and Microsoft Excel 2016. The results showed that the Quick Ratio and Total Asset Turnover partially but not significantly affected Firm Value. Meanwhile, the return on assets and debt-to-equity ratio significantly affect the firm's value. Simultaneously, the quick ratio, return on assets, debt-to-equity ratio, and total asset turnover significantly affect firm value.